2006
DOI: 10.1111/j.1745-7262.2006.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter/intra investigator variation in orchidometric measurements of testicular volume by ten investigators from five institutions

Abstract: The present study revealed significant differences in the results of estimation of testicular volume among the ten investigators, but intra-investigator variation was not considerable. Improved training and proper standardization of the measurement will be necessary before starting a multi-center study based on an andrological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
2
19
1
2
Order By: Relevance
“…Boys tended to overestimate their genital development stage, while girls’ assessments were generally more highly correlated with physician reports (Table V), a pattern that has been observed in several previous studies (32, 53, 56). However, using physician assessment as the gold standard has the implicit assumption that it is without error when there is evidence that this assumption is weak (5760). Another method of validating self-assessed sexual maturation status is comparing it with hormone-based measures of sexual maturation, although previous studies have been limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boys tended to overestimate their genital development stage, while girls’ assessments were generally more highly correlated with physician reports (Table V), a pattern that has been observed in several previous studies (32, 53, 56). However, using physician assessment as the gold standard has the implicit assumption that it is without error when there is evidence that this assumption is weak (5760). Another method of validating self-assessed sexual maturation status is comparing it with hormone-based measures of sexual maturation, although previous studies have been limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, substantial variation in assessments of skin fold thickness, waist circumference, and other anthropometry measures (63, 64), as well as blood pressure measurements (6567) have been demonstrated. The reliability of physician assessed sexual maturation status has generally been poor, especially for assessment of testicular volume (58, 60) and breast development (57), and is highly dependent on appropriate training (59, 68). Our results further suggest that physician assessments are not free of error.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, testicular volume can be assessed clinically by a variety of orchidometers, calipers and rulers or by US measurements of testis length, width and height, followed by multiplication by a constant. Although the orchidometer method is convenient for clinical use, experimental and clinical observations have shown that this method may not always be precise and consistent [10]. In fact, this method tends to overestimate the true volume, which might be caused by the inclusion of the epididymis or subcutaneous tissues [7,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…An additional centrifuged semen sample was confirmed to be azoospermic on the day of the planned TESE. Testicular volume was measured by physical examination using a standardized orchidometer by a single surgeon 9 and the average volume of the two testes was used for analysis. If only one testis was present then it was used in the calculation.…”
Section: Methodsmentioning
confidence: 99%